Content Marketing Strategy in Increasing Footabll School Students Interaction through Social Media - Ahmad Zaki Aulia; Nugraha Pramudya; Aang Curatman (Pusat Publikasi Nusantara, 2024)
Football School (SSB) is a place for students to learn and develop their football talents. In this digital era, social media has become an effective platform to reach and attract the interest of new and existing students to join SSB. The aim of this research is to analyze effective content marketing strategies in increasing SSB student interaction on social media. This research uses a qualitative research method with a case study approach. Data collection techniques in this research are observation, interviews and document analysis. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that an effective content marketing strategy can increase SSB student interaction on social media. This can help SSB to attract new students and increase the loyalty of old students. SSB needs to create interesting, informative and interactive content to encourage students to engage and participate in SSB activities.